Changes in seed oil and protein contents of maize cultivars at different positions on the ear in response to water limitation - Kazem Ghassemi-Golezani; Shabnam Heydari; Bahareh Dalil (Acta Agriculturae Slovenica)
A field experiment was carried out as split-split plot in 2014 to assess the effects of four irrigation treatments (irrigations after 60, 80, 100 and 120 mm evaporation, respectively) on oil and protein changes of maize cultivars (SC704, NS640 and DC303: Late, mid and early maturing cultivars, respectively) at different seed positions on the ear (upper, middle and lower positions on the ear). Overall, the highest seed yield was obtained from SC704, followed by NS640 and DC303 cultivars. Seed yield of all cultivars was higher at lower seed position on ear than at middle and upper parts of the ear under different irrigation treatments. The highest oil and protein yields were also recorded for seeds at lower position on the ear. Seed yield of all maize cultivars at various seed positions decreased with increasing irrigation intervals. Oil percentage decreased, but protein percentage increased with decreasing water availability. Water limitation decreased oil and protein yields of maize cultivars. Changes in protein and oil yields of maize cultivars at different seed positions and irrigation treatments were attributed to changes in seed yield.